Making Choices While Smelling, Tasting, and Listening: The Role of Sensory (Dis)similarity When Sequentially Sampling Products - Biswas, Dipayan; Labrecque, Lauren I.; Lehmann, Donald R.; Markos, Ereni (Journal of marketing, 2014)
Marketers are increasingly allowing consumers to sample sensory-rich experiential products before making purchase decisions. The results of seven experimental studies (two conducted in field settings, three conducted in a laboratory, and two conducted online) demonstrate that the order in which consumers sample products and the level of (dis)similarity between the sensory cues of the products influence choices. In the absence of any moderators, when sampling a sequence of sensory-rich experiential products (e.g., fragrances, chocolates, flavored beverages, music) with similar sensory cues (e.g., smell, taste, color, sound), consumers prefer the first product in the sequence. However, when sampling a sequence of products with dissimilar sensory cues, consumers prefer the last product. These findings (1) contribute to a better understanding of the role of sequential sensory cues on consumer choice formation, (2) have implications for effects related to sensory habituation and sensory trace fading, and (3) help resolve apparent inconsistencies in prior research on order effects in the context of choices for sequentially sampled experiential products.